Examining the feedback signals used in closed-loop control of intense laser fragmentation of CO+ - Wells, E.; Todt, Michael; Jochim, Bethany; Gregerson, Neal; Averin, R.; Wells, Nathan G.; Smolnisky, N. L.; Jastram, Nathan; McKenna, J.; Sayler, A. M.; Johnson, Nora G.; Zohrabi, M.; et al. (My University, 2009)
A closed-loop feedback system is used to determine the optimal pulse shapes for manipulating the branching ratio of carbon monoxide following ionization by an intense laser pulse. We focus on manipulating the C++O and C+O+ branching ratios of excited states of transient CO+. The feedback control system consists of a high resolution time-of-flight spectrometer coupled via a genetic feedback algorithm to an acousto-optical programmable dispersive filter that is incorporated into the ultrafast laser system. Using the spectrometer resolution to distinguish dissociation pathways and select a specific pathway to drive the algorithm, we are able to demonstrate enhanced control of some fragmentation channels. Principal control analysis indicates that the more specific feedback results in numerically simpler optimal pulse shapes. The combination of a more specific target and reduction in pulse complexity could lead to more straightforward investigations of the control mechanism. Analysis of the pulse shapes in conjunction with measurement of the fragment kinetic energy release distributions obtained from the optimized laser pulses is used to probe the dissociative ionization mechanisms.